Overview of EXL-50 research progress - Yuejiang Shi; Yumin Wang; Bing Liu; Xianming Song; Shaodong Song; Xinchen Jiang; Dong Guo; Di Luo; Xiang Gu; Tiantian Sun; Xianli Huang; Zhi Li; et al. (Nuclear Fusion)
XuanLong-50 (EXL-50) is the first medium-size spherical torus (ST) in China, with the toroidal field of 0.5 T at a major radius of 50 cm. Central Solenoid (CS)—free and non-inductive current drive via electron cyclotron resonance heating (ECRH) were the main physics research issue for EXL-50. Plasma currents from 50 kA to 180 kA were routinely achieved in EXL-50, with the current flattops sustained for up to or beyond 2 s. The current drive effectiveness on EXL-50 reached as high as 1 A W ^−1 for low-density discharges using 28 GHz ECRH alone for heating power less than 200 kW. The plasma current reached I p > 80 kA for high-density (>5 × 10 ^18 m ^−2 ) discharges with 150 kW 28 GHz ECRH. Higher performance discharge ( I p of about 120 kA and core density of about 1 × 10 ^19 m ^−3 ) was achieved with 150 kW 50 GHz ECRH. The plasma current in EXL-50 was mainly carried by the energetic electrons. The physics mechanisms for the solenoid-free ECRH current drive and the energetic electrons have also been investigated. Preliminary experimental results indicate that 100 kW of lower hybrid current drive waves can drive 20 kA of plasma current. Several boron injection systems were installed and tested in EXL-50, including B _2 H _6 gas puffing, boron powder injection, boron pellet injection. The upgrade of EXL-50, the EXL-50U, has begun experimental research to address these issues of ST proton-boron plasmas over a much wider parameter space.